What constitutes successful commissioning of transition from children's to adults' services for young people with long-term conditions and what are the challenges? An interview study. Issue 1 (11th September 2017) - Kolehmainen, Niina; McCafferty, Sara; Maniatopoulos, Gregory; Vale, Luke; Le-Couteur, Ann S; Colver, Allan
Abstract : Objective: We explored what constitutes successful commissioning for transition and what challenges are associated with this. We aimed: (1) to identify explicit and implicit organisational structures, processes and relationships that drive commissioning around transition; (2) to identify challenges faced by commissioners; and (3) to develop a conceptual model. Design: A qualitative interview study. Setting: Commissioning and provider organisations across primary and secondary care and third sector in England, UK. Participants: Representatives (n=14) from clinical commissioning groups, health and well-being boards and local authorities that commission national health services (NHS) for transition from children's to adults' services in England; NHS directors, general practitioners and senior clinicians (n=9); and frontline NHS and third sector providers (n=6). Results: Both commissioners and providers thought successful transition is personalised, coordinated and collaborative with a focus on broad life outcomes and actualised through building pathways and universal services. A multitude of challenges were described, including inconsistent national guidance, fragmented resources, incompatible local processes, lack of clear outcomes and professional roles and relationships. No single specific process of commissioning for transition emerged—instead complex, multi-layered, interactive processes were described. Conclusions: The findings indicate a need to consider more explicitly the impact of national policies and funding streams on commissioning for transition. Commissioners need to require care pathways that enable integrated provision for this population and seek ways to ensure that generalist community providers engage with children with long-term conditions from early on. Future research is needed to identify a core set of specific, meaningful transition outcomes that can be commissioned, measured and monitored.